(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
The differential cross-section for elastic scattering of positron by potassium atom have been calculated in intermediate energy range by using modified form of Born approximation. Born approximation has been modified and improved by taking into account the effect of nuclear interaction terms in the form of distorted wave. The impact of polarisation effect has been analysed. The results are compared with theoretical predictions of Khare and Vijayshri [3] .